Development of Musical Management System for Prodigy Studio - Dzahri, Ihsan; HAMZAH, MOHD HAMDI IRWAN (Applied Information Technology And Computer Science, 2023)
Musical management system for Prodigy Studio is a web-based event management system specifically design to handle events that are related to music and such. The development of this project is drive because of the current manual system the organization use. This project uses system prototyping methodology which involves developing a prototype into a final product. This system has its advantages and disadvantages that can be improve in the future